Chinese herbal medicine (Tangshen Formula) formula treatment of patients with diabetic kidney disease: a systematic review and meta-analysis - Zhao, Peng; Li, Yang; Sun, Yu; Yan, Shiwen; Su, Xiaqing; Sun, Yunying; Shi, Jiacheng; Zhu, Xiaoping (Frontiers in Endocrinology, 2025)
Background/ObjectiveDiabetic Kidney Disease (DKD) is a severe complication of diabetes mellitus and is one of the main causes of end-stage renal disease globally. Tangshen Formula (TSF) plays an important role in the treatment of DKD. The purpose of this study was to evaluate the efficacy and safety of TSF compound therapy in treating DKD patients with macroalbuminuria through systematic review and meta-analysis methods.MethodsMultiple databases, including PubMed, Embase, Cochrane Library and Web of Science, were searched to find eligible RCTs. The main outcome indicators included renal Primary Outcomes(UAER, 24h UP), Secondary Outcomes(eGFR and TCM system scores) and adverse events. Statistical analysis was conducted using RevMan 5.3 software, and the fixed-effect model or random-effect model was selected based on the heterogeneity among the studies.ResultsFrom 637 retrieved articles, 4 RCTs were finally included, involving 639 participants. The methodological quality of the included studies was generally good. The results indicate that, compared to the sole conventional placebo treatment, the use of TSF treatment after 24 weeks shows significant improvement in the experimental group over the control group, with UAER (MD=-15.94(95% CI: -30.67—1.22); P=0.03) and 24h UP (MD=-0.20(95% CI:-0.36—0.05);P=0.01); assessment of eGFR and scores showed no significant changes in the levels of these two indicators in patients, e GFR (MD=-4.95(95% CI: -11.52–1.62); P=0.47) and scores (MD=0.35(95% CI: -1.29–1.98);P=0.92). Microalbuminuria TSF group and placebo group UAER baselines were similar, with no statistical significance (OR= -4.32, 95% CI (-14.10, 5.48), P=0.29). Macroalbuminuria TSF group and placebo group UAER baselines were similar, with no statistical significance (OR =6.51, 95% CI (-6.27, 19.27), P=0.17). In the TMC compound therapy for DKD patients with massive proteinuria, the results show that the probability of adverse experiments in the intervention group was significantly lower than that in the control group (OR= 0.55 95% CI 0.30-1.03), P=0.79). There was no significant difference between the two groups.ConclusionIn summary, the findings of this meta-analysis suggest that TSF can provide effective assistance in reducing urinary protein and improving eGFR in DKD patients compared to conventional treatment. These benefits are consistently observed across both microalbuminuric and macroalbuminuric patient cohorts. Due to the limitations in the number and quality of the included studies, the preliminary findings necessitate further validation through high-quality, randomized controlled trials with larger sample sizes and longer follow-up periods to robustly confirm the efficacy of TSF and elucidate its precise mechanisms of action in DKD management.